Estudo dose-resposta do herbicida diuron[3-(3,4-diclorofenil)-1,1-dimetiluréia] no epitélio da bexiga de ratos Wistar machos - Cardoso, Ana Paula Ferragut [UNESP] (2010)
Diuron [3-(3,4-dichlorophenyl)-1,1-dimethylurea] is a herbicide that in a previous longterm study with Wistar rats fed at 2,500 ppm concentration showed high incidence of urothelial tumors in both genders. Accordingly, USEPA categorized Diuron as a “known/likely” human carcinogen. The accepted non-genotoxic mode of action (MOA) of Diuron encompasses urothelial necrosis induced by direct cytotoxicity, followed by regenerative cell proliferation and sustained urothelial hyperplasia that may favor neoplasia development. Scanning electron microscopy (SEM), light microscopy and labeling index are essentials tools for identification and classification of cytotoxic and proliferative changes in the bladder. The present study evaluated the dose-response of Diuron regarding urothelial lesions. Sixty male Wistar rats were fed Diuron for 20 weeks mixed in the diet at 0, 60, 125, 500, 1,250, or 2,500 ppm. Simple hyperplasia was significantly increased in the Diuron 1,250 and 2,500 ppm groups, and the cell proliferation at 2,500 ppm group. By SEM, the incidences and severity of lesions were significantly greater in the 500 and 1,250 ppm. Although numerically increased, the incidence of lesions in the 2,500 ppm group did not differ significantly from the control. The present study documented a doseresponse influence of Diuron on the rat urothelium, with a no observed effect level (NOEL) of 125 ppm.